Chemical constituents and free radical scavenging activity of extracts from Ocimum basilicum and Ocimum sanctum grown in Malaysia / Khairun Fadila Saaban - Khairun Fadila , Saaban (2017)
Ocimum basilicum (Thai basil) and Ocimum sanctum (Holy basil) both possess strong aromatic annual herb that is used in Asian cuisines and traditional medicine. The main constituents of Ocimum basilicum were identified to consist of estragole (> 35.71%), (E)-β-ocimene (> 1.47%), trans-α-bergamotene (> 0.83%), τ-cadinol (> 0.41%) eucalyptol (> 0.25%) and α-caryophyllene (> 0.07%) while Ocimum sanctum were mainly of eugenol methyl ether (> 34.34%), (E)-caryophyllene (> 7.91%), germacrene D (> 5.58%), β-elemene (> 4.22%) and copaene (> 1.49%). The chemical compounds were extracted by hydrodistillation, headspace-solid phase microextraction (HS-SPME) and solvent extraction. The free radical scavenging activity of Ocimum basilicum leaves showed IC50 values of 88 μg/mL and 1178 μg/mL for the methanol and dichloromethane extracts, respectively, while the methanol and dichloromethane extract of Ocimum sanctum showed a higher DPPH free radical scavenging activity with an IC50 value of 12 μg/mL and 369 μg/mL, respectively. Interspecies differences between the two species were determined by calculating Nei’s genetic distances with the value of 2.86. The calculated genetic distance between the two species showed that Ocimum basilicum and Ocimum sanctum are closely related species which share some of the same traits. Our results showed that Ocimum basilicum and Ocimum sanctum are promising to be used as natural antioxidants for food industry.